PENGARUH FAKTOR-FAKTOR ETERNAL TERHADAP KELAYAKAN FINANSIAL PROYEK PEMBANGUNAN JALAN TOL - Sitti Safiatus Riskijah (Prokons: Jurnal Teknik Sipil, 2018)
Highway construction project requires very large investment costs. Oftentimes, the highway construction encountered many obstacles, including external factors such as land acquisition which have an impact on a construction time regression, decreasing income, alteration of interest rates, and escalation of operational and maintenance costs. This study aims to determine the how much external factors influence on the financial feasibility of the highway construction.Financial analysis uses investment costs data, operational and maintenance costs, investment period, interest rate, the amount of private capital and loans, as well as the highway’s income. Determining financial eligibility criteria are based on following parameters; PP (Payback Period), NPV (Net Present value), BCR (Benefit Cost Ratio), and IRR (Internal Rate of Return). The sensitivity analysis was performed to determine the sensitivity level of external factor to financial feasibility, and impact analysis using linear regression analysis.The result of this study are as follows: 1) Judging from the financial aspects, highway construction projects are feasible due to PP < 18 years, NPV > 0 year, BCR > 1, IRR > MARR. 2) The external factor which have high level sensitivity and have positive influence (feasible) to the financial feasibility is the escalation of toll rate, while the factor with high level sensitivity yet have negative influence (infeasible) are the construction time regression, the decreasing income of land acquisition, as well as either the fallen or rising interest rate. Keywords: eexternal factors, financial feasibility, higway, influence, sensitivity level